The causal relationship between COVID-19 and increased intraocular pressure: A bidirectional two-sample Mendelian randomization study - Lin, Yi; Jiang, Bingcai; Cai, Yuanqing; Luo, Wangdu; Zheng, Changwei; Zhu, Xiaomin; Lin, Qianyi; Tang, Min; Li, Xiangji; Xie, Lin (Frontiers in Public Health, 2023)
Background: Coronavirus disease 2019 (COVID-19) has brought great challenges to the global public health system and huge economic burdens to society, the causal effect of COVID-19 and intraocular pressure was blank. Objective: This study aimed to explore the causal association between coronavirus disease (COVID-19) susceptibility, severity and criticality and intraocular pressure (IOP) by bidirectional Mendelian randomization (MR) analysis. Materials and methods: Genetic associations with COVID-19 susceptibility, severity and criticality were obtained from the COVID-19 Host Genetics Initiative. Genetic associations with IOP were obtained from GWAS summary data. The standard inverse variance weighted (IVW) method was used in the primary assessment of this causality. Other methods were also implemented in supplementary analyses. Finally, sensitivity analysis was performed to evaluate the reliability and stability of the results. Results: The results showed that COVID-19 susceptibility had null effect on IOP (β= 0.131; Se= 0.211; P= 0.533) as assessed by the IVW method. Moreover, the results revealed that COVID-19 severity, specifically, hospitalization due to COVID-19, had a positive effect on IOP (β= 0.228; Se= 0.116; P= 0.049). However, there were null effect of COVID-19 criticality on IOP (β= 0.078; Se= 0.065; P= 0.227). Sensitivity analysis showed that all the results were reliable and stable. The reverse MR analysis revealed that there was null effect of IOP on COVID-19. Conclusions: We demonstrated that hospitalization due to COVID-19 might increase IOP; therefore, greater attention should be given to monitoring IOP in inpatients with COVID-19.